A bibliometric analysis of HER2-positive breast cancer: 1987–2024 - Ali-Thompson, Sherlissa; Daly, Gordon R.; Dowling, Gavin P.; Kilkenny, Conor; Cox, Luke; McGrath, Jason; AlRawashdeh, Ma’en M.; Naidoo, Sindhuja; Power, Colm; Hill, Arnold D. K. (Frontiers in Oncology, 2024)
The over-amplification of human epidermal growth factor (HER2) in breast cancer (BC) has been the subject of numerous research publications since its discovery in 1987. This is the first bibliometric analysis (BA) conducted on HER2-positive (HER2+) BC. The purpose of this BA is to analyse the published research on HER2+ BC from 1987-2024, highlighting the most significant scientific literature, the main contributing authors and journals and evaluating the impact of clinical and lab-based publications on HER2+ BC research.Web of Science Core Collection (WoS) was searched using terms 'Breast cancer' OR 'Breast carcinoma' OR 'Breast tumour" AND 'HER2 positive' OR 'HER2+'. The search was limited by publication year (1987-2024) and only full English articles were included. WoS returned 7,469 relevant results and from this dataset a bibliometric analysis was conducted using the 'analyze results' and 'journal citation report' functions in WoS and the VoS viewer 1.6.16 software to generate bibliographic coupling and co-citation analysis of authors.The analysis encompassed a total of 7,469 publications, revealing a notable increase in the annual number of publications, particularly in recent years. The United States, China, Italy, Germany and Spain were the top five most prolific countries. The top five significant institutions which published HER2+